Comparing Pretransplant and Posttransplant Outcomes When Choosing a Transplant Center: Focus Groups and a Randomized Survey. Issue 1 (January 2020) - Schaffhausen, Cory R.; Bruin, Marilyn J.; Chu, Sauman; Wey, Andrew; McKinney, Warren T.; Snyder, Jon J.; Lake, Jack R.; Matas, Arthur J.; Kasiske, Bertram L.; Israni, Ajay K.
Abstract : Background: In response to calls for an increased focus on pretransplant outcomes and other patient-centered metrics in public reports of center outcomes, a mixed methods study evaluated how the content and presentation style of new information influences decision-making. The mixed methods design utilized qualitative and quantitative phases where the strengths of one method help address limitations of the other, and multiple methods facilitate comparing results. Methods: First, a series of organ-specific focus groups of kidney, liver, heart, and lung patients helped to develop and refine potential displays of center outcomes and understand patient perceptions. A subsequent randomized survey included adult internet users who viewed a single, randomly-selected variation of 6 potential online information displays. Multinomial regression evaluated the effects of graphical presentations of information on decision-making. Results: One hundred twenty-seven candidates and recipients joined 23 focus groups. Survey responses were analyzed from 975 adults. Qualitative feedback identified patient perceptions of uncertainty in outcome metrics, in particular pretransplant metrics, and suggested a need for clear guidance to interpret the most important metric for organ-specific patient mortality. In the randomized survey, only respondents who viewed a note indicating that transplant rate had the largest impact on survival chose the hospital with the best transplant rate over the hospital with the best posttransplant outcomes (marginal relative risk and 95% confidence interval, 1.16 1.501.95 ). Conclusions: The presentation of public reports influenced decision-making behavior. The combination of qualitative and quantitative research helped to guide and enhance understanding of the impacts of proposed changes in reported metrics. Abstract : Supplemental Digital Content is available in the text.